Impact of financial literacy on investment decisions: evidence from the nepal stock market - Ghimire, Shiva Raj; Agarwal, Dr. Nirdosh Kumar; Chaurasiya, Dr. Sneha (Journal of Commerce, Management, and Tourism Studies, 2025)
This study aims to investigate the impact of financial literacy on investment decision-making in the Nepal Stock Market. It particularly focuses on identifying disparities in financial literacy levels among investors and provides insights to inform policymakers and stakeholders in enhancing financial education programs across Nepal. A causal-comparative research design was employed, targeting investors in the Kathmandu Valley and representing all seven provinces of Nepal. Using a convenience sampling method, data were collected from 250 investors through a structured questionnaire. Analytical methods like descriptive statistics, correlation analysis, and multivariate regression were used to examine how different aspects of financial literacy—like knowledge, awareness, experience, skills, ability, and goals—affect investment decisions. The findings reveal that financial literacy significantly influences investment behavior, though the extent of influence varies across its components. Financial Knowledge (FKW) had a notably strong positive impact on investment decisions. Financial Awareness (FAW), Financial Experience (FEX), and Financial Skills (FSK) showed moderate effects. Financial Capability (FCP) emerged as a key determinant, while Financial Goals (FGL) exerted a substantial influence on decision-making. This study provides empirical evidence of the role of financial literacy in shaping investment behavior within the Nepalese context—a relatively underexplored area. It offers practical recommendations for enhancing financial literacy through personalized education programs, accessible learning resources, and institutional integration. These insights are valuable for fostering a more informed, rational, and inclusive investment environment in Nepal.